A heavy-duty magnetorheological fluid mount with flow and squeeze model. (22nd June 2021) - Huang, Jincheng; Li, Shaoqi; Zhou, Yuxian; Xu, Tiancheng; Li, Yancheng; Wang, Huixing; Wang, Shuguang
Abstract: In this paper, a new type of heavy-duty magnetorheological fluid (MRF) mount is proposed and experimentally investigated. The MRF mount with both annular and radial channels are based on two operating modes: flow mode and squeeze mode. The combined paths can lengthen the MRF valve and hence maximize the MR effect in flow mode. A mechanical model is established to institutively predict the maximum damping force that the device can achieve. Magnetic field distribution of the MRF mount is then evaluated based on finite element analysis. Both squeeze and flow regions can obtain magnetic field intensities up to 0.742 T and 0.7 T under 1 A current, respectively. Finally, the quasi-static and dynamic tests of MRF mount under different loading conditions (frequency, amplitude, current) are performed and the results showed that the proposed MRF mount can provide large damping force up to 18.843 kN and wide tunable range (719% increase on damping force at 0.1 Hz with 2 mm amplitude).